2008
DOI: 10.1152/ajprenal.00065.2008
|View full text |Cite
|
Sign up to set email alerts
|

Regression of glomerulosclerosis in subtotally nephrectomized rats: effects of monotherapy with losartan, spironolactone, and their combination

Abstract: Piecha G, Koleganova N, Gross M-L, Geldyyev A, Adamczak M, Ritz E. Regression of glomerulosclerosis in subtotally nephrectomized rats: effects of monotherapy with losartan, spironolactone, and their combination. Am J Physiol Renal Physiol 295: F137-F144, 2008. First published April 23, 2008 doi:10.1152/ajprenal.00065.2008.-Angiotensin II accelerates and renin-angiotensin system blockade halts progression; blockade with high doses even reverses established glomerulosclerosis. Aldosterone also accelerates progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 31 publications
2
32
0
Order By: Relevance
“…Unlike their effects on podocyte injury, however, their combined effects were not observed in glomerular sclerosis. Although these data are consistent with those of Piecha et al (2008) who showed that adding spironolactone to an ARB did not improve the regression of glomerular sclerosis in subtotally nephrectomized rats, it is unclear why the combined effects of an ARB and an MR blocker are apparent on podocyte injury but not on glomerular sclerosis. However, these effects may be dependent on complex interactions among several factors that mediate mesangial matrix expansion.…”
Section: Raas Blockade and Podocyte Injury In Diabetes 1077supporting
confidence: 88%
“…Unlike their effects on podocyte injury, however, their combined effects were not observed in glomerular sclerosis. Although these data are consistent with those of Piecha et al (2008) who showed that adding spironolactone to an ARB did not improve the regression of glomerular sclerosis in subtotally nephrectomized rats, it is unclear why the combined effects of an ARB and an MR blocker are apparent on podocyte injury but not on glomerular sclerosis. However, these effects may be dependent on complex interactions among several factors that mediate mesangial matrix expansion.…”
Section: Raas Blockade and Podocyte Injury In Diabetes 1077supporting
confidence: 88%
“…15 The control animals received vehicle alone. Body weight and blood pressure (by tail plethysmography in conscious animals 24 h after the last dose) were measured at regular intervals.…”
Section: Materials and Methods Animals And Subtotal Nephrectomymentioning
confidence: 99%
“…We have shown earlier that the calcimimetic R-568 decreases albuminuria in subtotally nephrectomized rats. 15 Therefore, it was the purpose of this study to further evaluate the effects of the calcimimetic R-568 on cardiac mass, contractility, capillary density, interstitial fibrosis, and the expression of pathophysiologically relevant molecules in subtotally nephrectomized rats.…”
mentioning
confidence: 99%
“…These studies investigated stereological parameters such as estimation of glomerular number and volume, volume of tubules, and volume of renal cortical interstitium. [24,25] However, none of these studies mentioned the effects of neuroleptics on the kidney. In our study, many structures of the kidney were stereologically analyzed and detailed with histological examinations.…”
Section: Discussionmentioning
confidence: 99%